2022
DOI: 10.1049/ipr2.12439
|View full text |Cite
|
Sign up to set email alerts
|

An algorithm to detect overlapping red blood cells for sickle cell disease diagnosis

Abstract: In Africa, Uganda is among the countries with a high number of babies (20,000 babies) born with sickle cell, contributing between 6.8% of the children born with sickle cell every year worldwide and approximately 4.5% of the children born with hemoglobinopathies worldwide. It is estimated that by 2050, sickle cell cases will increase by 30% if no intervention is put in place. To facilitate early detection of sickle cell anaemia, medical experts employ machine learning algorithms to detect sickle cell abnormalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The concept of transfer learning has been widely applied in the detection of sickle cells for example a study by (de Haan et al, 2020) utilised deep learning techniques in their framework for detecting sickle cell using blood smears taken with smartphone microscope. The framework achieved 98% accuracy, also (Vicent et al, 2022) reported 98.18% accuracy automation detection of overlapping red blood cells for sickle cells diagnosis. (Arishi, Alhadrami, & Zourob, 2021) conducted a review study on current and emerging techniques for sickle cell disease detection and highlighted potential methods for early diagnosis of sickle cell disease.…”
Section: Table 1: Model Performance On Training Dataset Table 2: Mode...mentioning
confidence: 72%
See 2 more Smart Citations
“…The concept of transfer learning has been widely applied in the detection of sickle cells for example a study by (de Haan et al, 2020) utilised deep learning techniques in their framework for detecting sickle cell using blood smears taken with smartphone microscope. The framework achieved 98% accuracy, also (Vicent et al, 2022) reported 98.18% accuracy automation detection of overlapping red blood cells for sickle cells diagnosis. (Arishi, Alhadrami, & Zourob, 2021) conducted a review study on current and emerging techniques for sickle cell disease detection and highlighted potential methods for early diagnosis of sickle cell disease.…”
Section: Table 1: Model Performance On Training Dataset Table 2: Mode...mentioning
confidence: 72%
“…(Das, Meher, Panda, & Abraham, 2019) provides a detailed methodological review about deep learning technique and tools used to detect sickle cell disease. (Vicent et al, 2022) developed an algorithm to detect presence of sickle cells in overlapping red blood cells. In their method, canny edge and double threshold machine learning techniques were used to separate overlapping cells of digital blood smears.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Azimuthal Walsh filters have also been used to modify the far-field diffraction pattern in a customized way [12,13]. Deep Convolutional Neural Networks and image processing techniques have also been applied to sickle cell detection [14,15]. Also, it is known that often any irregularity in the geometry of a cell implies the advent of some disease in it.…”
Section: Introductionmentioning
confidence: 99%